Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Make A Match di Sekolah Dasar - Salsabilla, Nurul; Hamimah, Hamimah (Universitas Negeri Padang, 2023)
The research on integrated thematic learning in class III is motivated by the low student learning outcomes. This study aims to describe the improvement of students learning outcomes in integrated thematic learning using the Cooperative Learning Model Type Make A Match in class III SD Negeri 14 Belanti Barat Kota Padang. This research is a classroom action research using qualitative and quantitative approaches. The research was conducted in two cycles with the research procedures consisting of planning, implementation, observation, and reflection. The subjects of this research were the teacher and 29 students of class III SD Negeri 14 Belanti Barat in the second semester of the academic year 2022/2023. The result of the study showed that in cycle I, the average percentage of the lesson plan evaluation was 83,75% (B), increasing in cycle II to 92,5% (SB). The teacher aspect evaluation in cycle I obtained an average percentage of 82,5%(B), increasing in cycle II to 95% (SB). The student aspect evaluation in cycle I obtained an average percentage of 82,5% (B), increasing in cycle II to 95% (SB). The learning outcomes aspect evaluation in cycle I obtained an average percentage of 78,65 (C), increasing in cycle II to 88,35 (B).